Detection and determination of C12‐, C14‐, C16‐alkyldimethylamines in human blood using gas chromatography–mass spectrometry. (28th April 2022) - Brousa, Evdokia; Mastrogianni, Orthodoxia; Orfanidis, Amvrosios; Zaggelidou, Eleni; Raikos, Nikolaos; Gika, Helen G.
Abstract : Rationale: N, N ‐Dimethyldodecylamine is produced from lauryl alcohol and dimethylamine. C12–C16 alkyldimethylamines are used as intermediates for the manufacture of amineoxides and quaternary amino compounds. In the present study a gas chromatography–mass spectrometry (GC/MS) method for the determination of C12–C16 alkyldimethylamines in blood was developed and validated. The reason for this study was the detection of the above compounds in the postmortem blood sample of a fatal suicide case. Methods: Analysis of amines was performed using a gas chromatograph (Agilent Technologies 7890A) with an MS 5975C inrXL, EI/CI MSD with triple‐axis detector in selected ion monitoring mode, after liquid–liquid extraction. Four different organic solvents (butyl acetate, ethyl acetate, n ‐hexane and n ‐heptane) were used for the optimization of the extraction procedure, resulting in ethyl acetate being the solvent of choice for the extraction procedure. A QuEChERS step was applied (20 mg of MgSO4, 5 mg of NaCl) to 1 mL of blood and pH was adjusted at 12 (K2 CO3 buffer solution). After the addition of the extraction solvent, samples were vortexed, centrifuged and directly injected into the GC/MS system. Results: In validation, the method was found to be selective and sensitive (limit of detection from 0.3 to 0.5 ng/mL, limit of quantitation from 10.0 to 20.0 ng/mL), whilst validation included recovery, stability, accuracy and precision (relative standard deviation). Validation results were found satisfactory: intra‐ and interday precision ranged from 0.4% to 2% and from 0.6% to 1.9% respectively, while intra‐ and interday accuracy ranged from 87% to 109% and from 86% to112.8%. C12–C16 alkyldimethylamines were detected in blood samples at a concentration of 8.39 μg/mL (C12), 3.01 μg/mL (C14) and 0.42 μg/mL (C16). Conclusions: A rapid, sensitive and reliable method was developed for the determination of C12–C16 alkyldimethylamines in postmortem blood, after optimization of the sample preparation procedure, and finally successfully applied to a real postmortem blood sample from a fatal case involving these compounds.